Chemical composition of rocks and minerals from the Central Atlantic fracture zones - Pushcharovsky, Yury M; Peyve, Alexander A; Raznitsin, Yury N; Bazilevskaya, Elena S (Supplement to: Pushcharovsky, YM et al. (1995): The Central Atlantic Fracture Zones. Geological Institute of the Russian Academy of Sciences, Transactions, vol. 495. Moscow, GEOS Publ. (S.D. Sokolov, Ed.), 164 pp, 1995)
The monograph summarizes materials on geology and deep structure of the Central Atlantic fracture zones. These materials have been obtained during eight expeditions of R/V ''Akademik Nikolaj Strakhov''. The studies have been based on the integrated geological approach. As a result, many new tectonic, magmatic, metallogenic and historical-geological features of these phenomenal structures of the deep ocean have been revealed.